2006
DOI: 10.1021/np050513p
|View full text |Cite
|
Sign up to set email alerts
|

Interference by Naturally Occurring Fatty Acids in a Noncellular Enzyme-Based Aromatase Bioassay

Abstract: Natural product drug discovery efforts frequently utilize noncellular screening assays. Fatty acids are commonly found in natural product extracts, and some have been shown to interfere with noncellular assays. Several pure fatty acids were tested using a noncellular aromatase assay, with the unsaturated analogues showing strong inhibitory activity, while the saturated analogues were inactive. Unsaturated fatty acids were further tested against SK-BR-3 hormone-independent human breast cancer cells that overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Furthermore, unsaturated fatty acids with more than one double bond (e.g., linoleic acid, conjugated linoleic acid, and linolenic acid) are more potent than those with only one double bond (e. g., oleic acid). These results are similar to those reported recently by Balunas et al (49). The article by Balunas et al also indicated that tested unsaturated fatty acids, including linoleic acid, were found to be inactive when tested with in-cell aromatase assay using SK-BR-3 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, unsaturated fatty acids with more than one double bond (e.g., linoleic acid, conjugated linoleic acid, and linolenic acid) are more potent than those with only one double bond (e. g., oleic acid). These results are similar to those reported recently by Balunas et al (49). The article by Balunas et al also indicated that tested unsaturated fatty acids, including linoleic acid, were found to be inactive when tested with in-cell aromatase assay using SK-BR-3 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Two other fatty acids, (10E,12Z)-9-hydroxy-10,12-octadecadienoic acid (149) and docosapentaenoic acid (146) [152], showed weak aromatase inhibitory activity in microsomal testing [151]. However, though several unsaturated fatty acids exhibited strong aromatase inhibitiory activity during initial screening they were found to be inactive in cellular aromatase testing [152]. In bioassay-guided studies on natural product extracts for aromatase inhibition activity, fatty acids may be regarded as "interfering" substances, since they are active in noncellular, enzyme-based aromatase assays but do not inhibit aromatase in secondary cellular testing [152].…”
Section: Natural Product Compounds Tested For Aromatase Inhibitionmentioning
confidence: 99%
“…Using the categories delineated above, one of the fatty acids, (10E,12Z)-9-oxo-10,12-octadecadienoic acid (154) isolated from Urtica dioica L. (stinging nettle) showed moderate aromatase inhibitory activity [151]. Two other fatty acids, (10E,12Z)-9-hydroxy-10,12-octadecadienoic acid (149) and docosapentaenoic acid (146) [152], showed weak aromatase inhibitory activity in microsomal testing [151]. However, though several unsaturated fatty acids exhibited strong aromatase inhibitiory activity during initial screening they were found to be inactive in cellular aromatase testing [152].…”
Section: Natural Product Compounds Tested For Aromatase Inhibitionmentioning
confidence: 99%
“…For instance, plant-derived compounds are widely used as anticancer agents, such as bisin- dole (vinca) alkaloids, camptothecins, epipodophyllotoxins, and taxanes (25). The focus in cancer control has been on the search for safer anticancer agents, with higher patient acceptability.…”
Section: Discussionmentioning
confidence: 99%